COMPETENCES OF TEACHERS AND STUDENTS IN ICT - LUKÁČOVÁ, Danka (Journal of Technology and Information Education, 2011)
Improving the quality of education in universities is possible only if we know the contents of educational curricula, which are confronted with a real Graduate. Investigators KEGA are dealing with the role of the ability of teachers and students to use ICT in practice - as in teacher training, as well as teaching itself. The article presents the results of the research conducted by questionnaire. [PUBLICATION ABSTRACT]